Supporting the creative industries through the AI turn: A comparative analysis of Scottish policy and the needs of Scotland’s creative practitioners - Suzanne R. Black; Caterina Moruzzi; Nicola Osborne; Melissa Terras; Frauke Zeller (PLoS ONE, 2026)
In the creative industries (one of the largest UK sectors, which operates at the juncture of business, technology and the arts) creative practitioners are not only consumers of Artificial Intelligence (AI), but also its developers, originators and innovators. This has material consequences for how creative work is performed, valued and understood, as well as global consequences for business structures, the environment, equality and power discrepancies. We take Scotland as a case study for how governmental policy addresses the challenges of AI for the creative industries by comparing Scotland’s Artificial Intelligence Strategy with data gathered from grass roots creative industries practitioners in Scotland through workshops and a survey. We identify differences between the priorities of Scotland’s Artificial Intelligence Strategy and the creative industries, as well as a lack of advice specific to the needs of the creative industries, and offer recommendations on how to put creatives at the heart of AI developments.